Pengaruh Intellectual Capital terhadap Nilai Perusahaan pada Sektor Industri Dasar dan Kimia di Bursa Efek Indonesia Tahun 2020-2022 - Mishelei Loen, SE., M.Si. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study aims to determine the partial or simultaneous effect of intellectual capital proxied by Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA), on Company Value. The data used in this research is secondary data. The data source used in this study was obtained from the annual financial reports of manufacturing companies in the Chemical Basic Industry sector listed on the Indonesia Stock Exchange for the period 2020–2022, which were downloaded from the Indonesia Stock Exchange website, namely www.idx.co.id, which will then be processed using SPSS software version 26. The population used in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2022. The test results show that Value Added Capital Employed (VACA) has a positive and significant influence on firm value. Value Added Human Capital (VAHU) has a positive and significant effect on firm value. Structural Capital Value Added (STVA) has no effect on firm value. Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA) simultaneously have a significant effect on firm value.